Immune Responses in the Central Nervous System Are Anatomically Segregated in a Non-Human Primate Model of Human Immunodeficiency Virus Infection - Tavano, Barbara; Tsipouri, Vicky; Hardy, Gareth A. D.; Royle, Caroline M.; Keegan, Michael R.; Fuchs, Dietmar; Patterson, Steven; Almond, Neil; Berry, Neil; Ham, Claire; Ferguson, Deborah; Boasso, Adriano (Frontiers in Immunology, 2017)
The human immunodeficiency virus (HIV) accesses the central nervous system (CNS) early during infection, leading to HIV-associated cognitive impairment and establishment of a viral reservoir. Here we describe a dichotomy in inflammatory responses in different CNS regions in simian immunodeficiency virus (SIV)-infected macaques, a model for HIV infection. We found increased expression of inflammatory genes and perivascular leukocyte infiltration in the midbrain of SIV-infected macaques. Conversely, the frontal lobe showed downregulation of inflammatory genes associated with interferon-gamma and interleukin-6 pathways, and absence of perivascular cuffing. These immunologic alterations were not accompanied by differences in SIV transcriptional activity within the tissue. Altered expression of genes associated with neurotoxicity was observed in both midbrain and frontal lobe. The segregation of inflammatory responses to specific regions of the CNS may both account for HIV-associated neurological symptoms and constitute a critical hurdle for HIV eradication by shielding the CNS viral reservoir from antiviral immunity.